Molecular Patterns of Resistance Among Helicobacter pylori Strains in South-Western Poland - Bińkowska, Aldona; Biernat, Monika Maria; Łaczmański, Łukasz; Gościniak, Grażyna (Frontiers in Microbiology, 2018)
Treatment failure of Helicobacter pylori infection is caused mainly by progressive antibiotic resistance among H. pylori strains. In Poland, the prevalence of H. pylori strains resistant to metronidazole is higher than in other developed countries, reaching almost 50%, and resistance to clarithromycin is as high as 30% and is still increasing, contributing to the failure of first-line therapy in approximately 70% of patients. Moreover, the introduction of levofloxacin to eradication therapy of H. pylori infection quickly led to the emergence of resistant strains. Therefore, a necessary approach in microbiological diagnostics of H. pylori infection should be determination of susceptibility of H. pylori strains before the eradication treatment. The aim of this study was to evaluate the molecular mechanisms of resistance among 170 H. pylori strains to clarithromycin and levofloxacin by using polymerase chain reaction (PCR) and classical sequencing of DNA fragments. Results: Among examined strains, 26% were fully sensitive and 74% were resistant to at least one of the tested antibiotics. The A2143G point mutation was found in 72% of clarithromycin-resistant strains. The most common mutation, present in 40% of H. pylori strains resistant to levofloxacin, was a change at position 91 of gyrA. Conclusions: The increasing number of point mutations in the 23s rRNA gene leads to an increase in the rates of antimicrobial resistance. Presence of the GCG allele at position 122 of the gyrA gene may cause an 8-fold increase in risk of development of resistance to levofloxacin.